Automotive ergonomics - Bubb, Heiner; Bengler, Klaus; Grünen, Rainer E.; Vollrath, Mark (Springer, 2021)
Ergonomics teaches how to design technology in such a way that it is optimally adapted to the needs, wishes and characteristics of the user. In this context, the concept of the human-machine system has become established. In a systematic way and with a detailed view of the complicated technical and perceptual psychological and methodological connections, this book explains the basics of automotive ergonomics with numerous examples.